CANVA-BASED LEARNING AND LEARNING STYLES: EXPERIMENTAL INSIGHTS INTO ISLAMIC EDUCATION LEARNING OUTCOMES IN PRIMARY SCHOOLS - L, Erawati; Tahir, M. Yusuf; Rapi, Muh. (Abjadia : International Journal of Education, 2025)
This study aims to examine the effect of using Canva-based learning media on learning outcomes of Islamic Religious Education (PAI) in class III SDIT Al-Insan Pinrang, as well as how it relates to individual learning styles of students. The problem raised is the extent to which the use of Canva media can improve students' learning outcomes compared to PowerPoint media, taking into account visual, auditory, and kinesthetic learning styles. This study used a quantitative approach with a quasi-experimental non-equivalent control group design, where learners were divided into two groups, namely the experimental group using Canva and the control group using PowerPoint. The research design also involved a 2x3 factorial analysis to see the interaction between learning media and learning styles. Data was collected through pre-test and post-test to measure learning outcomes, as well as a questionnaire to identify learners' learning styles. Hypothesis testing was conducted using two independent samples t-test, one-way ANOVA, and Kruskal-Wallis to see the differences between experimental and control groups, as well as differences based on learning styles. The results showed that the use of Canva had a significant effect on PAI learning outcomes, especially for students with visual and kinesthetic learning styles. However, there was no significant difference between the auditory learning style groups using Canva and PowerPoint. This finding reinforces the importance of considering learning styles in choosing learning media, and shows that visual design-based learning media, such as Canva, can increase learners' motivation and active participation, especially in learning that requires greater visual engagement. This research is beneficial for the development of more adaptive and effective learning methods in primary schools.